2003
DOI: 10.1007/s00497-003-0188-2
|View full text |Cite
|
Sign up to set email alerts
|

A defective pollen-pistil interaction contributes to hamper seed set in the parthenocarpic fruit tomato mutant

Abstract: In the parthenocarpic fruit (pat) tomato mutant, parthenocarpy is associated with partial aberrations of stamens (shortness and carpelloidy) and ovules (defective integument growth) that contribute to impair seed set. However, these do not seem to be the only reasons for seed infertility because hand-pollination fails to restore seed set in ovaries where a fraction of the ovules are still morphologically normal. Therefore, it is conceivable that other unreported defects occur during the reproductive process in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
0
22
0
3
Order By: Relevance
“…Failures in pollination are thought to be widespread in plants and a common cause of low seed set (Wilcock and Neiland 2002;Marta et al 2004;Pellegrino et al 2005;Hodnett et al 2005;Ram et al 2006;Lee et al 2008;Spielman and Scott 2008). For instance, Mazzucato et al (2003) indicated that a defective pollen-pistil interaction was a main factor leading to low seed set in the parthenocarpic fruit tomato mutant. The experiments described here demonstrated that in the cross between D. grandiflorum 'Yuhuaxingchen' and D. nankingense very few pollen grains germinated on stigmas and most pollen tubes failed to penetrate Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Failures in pollination are thought to be widespread in plants and a common cause of low seed set (Wilcock and Neiland 2002;Marta et al 2004;Pellegrino et al 2005;Hodnett et al 2005;Ram et al 2006;Lee et al 2008;Spielman and Scott 2008). For instance, Mazzucato et al (2003) indicated that a defective pollen-pistil interaction was a main factor leading to low seed set in the parthenocarpic fruit tomato mutant. The experiments described here demonstrated that in the cross between D. grandiflorum 'Yuhuaxingchen' and D. nankingense very few pollen grains germinated on stigmas and most pollen tubes failed to penetrate Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Several tomato mutant genotypes resulting in parthenocarpic fruit growth have been described, of which pat (Mazzucato et al, 2003), pat2 (Philouze and Maisonneuve, 1978), pat3, and pat4 (Nuez et al, 1986) are the best characterized. In contrast to the Chs RNAi tomato, parthenocarpic fruit development of all these pat mutants is independent of pollination.…”
Section: Discussionmentioning
confidence: 99%
“…In pat tomato mutants, there are partial aberrations of the stamens and ovules, and fertilization is strongly inhibited even where the ovules appear normal due to abnormalities in the pollen tube-ovary interaction (Mazzucato et al, 1998(Mazzucato et al, , 2003, indicating that pat may result from the mutation of a putative gene with homeotic functions. SEPATALA (SEP) is a MADS box gene that interacts with other MADS box genes to control the development of each floral whorl in Arabidopsis.…”
mentioning
confidence: 99%